Newly recognized Anaplasma sp. in erythrocytes from Gopher Tortoises (Gopherus polyphemus). (14th February 2020) - Raskin, Rose E.; Crosby, Francy L.; Jacobson, Elliott R.
Abstract: Background: In 2015, a previously unrecognized intracytoplasmic erythrocytic inclusion was discovered in anemic wild‐caught adult gopher tortoises ( Gopherus polyphemus ). Subsequently, molecular diagnostics revealed this inclusion to be a novel Anaplasma sp. Objectives: The goal of this study was to morphologically characterize these erythrocytic inclusions by light and transmission electron microscopy (TEM). Methods: Blood samples were taken from two car‐injured wild‐caught gopher tortoises for the preparation of Wright‐Giemsa stained smears and TEM specimens. CBC data were serially performed and morphologically examined during treatment periods. Results: Studies revealed a moderate to severe anemia with moderate regeneration as indicated by polychromasia and the presence of immature erythroid precursors. In addition, on light microscopy, one to two variably‐sized round basophilic stippled paracentral erythrocytic inclusions were present per cell in both animals and involved 10%‐25% of erythrocytes. TEM identified the intraerythrocytic inclusions as discrete membrane‐bound cytoplasmic vacuoles (morulae) containing membrane‐bound bacterial subunits that were of variable size, shape, and electron density. Serial hematologic data indicated complete remission of the infection in response to a single long‐term course of doxycycline. Conclusions: The presence of a regenerative anemia in gopher tortoises from Florida revealed a newly recognized bacterial species that has morphologic characteristics similar to members of the genus Anaplasma .